Irish Poets: Keepers of National Lore - Asst. Prof. Dr. Amal Nasser Frag (الأستاذ, 2019)
This paper discusses three noteable Irish poets: Augustine Joseph Clarke (1896-1974), Richard Murphy  (1927- ), and Patrick  Kavanagh  (1904–1967), who are considered as keepers of national lore of Irland. It explains these poets’ contribution to world literature through the renewal of Irish myths, history, and culture. Irish poets tackle the problems of Irish people in the present in a realistic way by criticising the restrictions imposed on the Irish people in their society.Augustine Joseph Clarke’s poems present a deep invocation of Irish past and landscape. While Richard Murphy offers recurring images of islands and the sea. He explores the personal and communal legacies of history, as many of his poems reveal his attempts to reconcile his Anglo-Irish background and education with his boyhood desire to be, in his words, “truly Irish”. Patrick  Kavanagh was not interested in the Irish Literary Renaissance Movement that appeared and continued to influence many Irish writers during the twentieth century which called for the revival of ancient Irish culture, language, literature, and art. He, unlike the Irish revivalists who tried to revive the Gaelic language as the mother tongue of the Irish people like Dillon Johnston and Guinn Batten, uses a poetic language based on the day-to-day speech of the poet and his community rather than on an ideal of compensation for the fractures in his country’s linguistic heritage. The paper conculdes with the importance of the role of the Irish poet as a keeper and a gurdian of his national lore and tradition